Sexual dimorphism in the synchrony of joint growth hormone and cortisol dynamics in children with classic 21-hydroxylase deficiency. - Charmandari, E; Pincus, S; Matthews, DR; Johnston, A; Brook, C; Hindmarsh, P (2003)
In humans, growth hormone (GH) and cortisol are secreted in a pulsatile fashion and a mutual bidirectional interaction between the GH/insulin-like growth factor (IGF)-I axis and hypothalamic-pituitary-adrenal (HPA) axis has been established. Classic congenital adrenal hyperplasia (CAH) is characterized by a defect in the synthesis of glucocorticoids and often mineralocorticoids, and adrenal hyperandrogenism. In view of the sexually dimorphic pattern in GH secretion, we investigated the GH-cortisol bihormonal secretory dynamics in male and female children with classic CAH. Thirty-eight children with classic 21-hydroxylase deficiency (M: 13, F: 25; age range: 6.1-18.8 yr) were studied prospectively. Serum GH and cortisol concentrations were determined at 20 min intervals for 24 hours. The irregularity of GH and cortisol pattern was assessed using approximate entropy (ApEn), a scale- and model-independent statistic. The synchrony of joint GH-cortisol dynamics was quantified using the cross-ApEn statistic. Cross-correlation analysis of GH and cortisol concentrations was computed at various time lags covering the 24-h period. There was no gender difference in mean 24-hour serum GH (males vs females: 5.25 +/- 4.72 vs 4.44 +/- 2.64 mIU/l) or cortisol (156.2 +/- 44.6 vs 172.0 +/- 58.5 nmol/l) concentrations. For GH, ApEn values were significantly higher in females (0.66 +/- 0.14) than in males (0.53 +/- 0.16) (p = 0.009). No difference in cortisol ApEn values was noted between sexes (0.53 +/- 0.21 vs 0.54 +/- 0.12). Cross-ApEn values of paired GH-cortisol, with cortisol leading GH, were significantly higher in females (0.94 +/- 0.14) than in males (0.83 +/- 0.20) (p = 0.03). These findings suggest that females with classic 21-hydroxylase deficiency have a more irregular pattern of GH secretion and a more asynchronous joint GH and cortisol dynamics than their male counterparts.